Peliculização de sementes de tomate associada ao paclobutrazol - Melo , Aniela Pilar Campos de (2013)
Seed treatment with paclobutrazol should be enhanced and coating technologies, such as film coating can be applied uniformly and promising to fix this regulator in the seed coat without allowing a contact damaging the embryo. Thus, the objective of this study was to evaluate the technical feasibility of the film coating tomato seeds with paclobutrazol on seed physiological potential and the implications on the growth of seedlings. The research was carried out in the Laboratory of the “Setor de Horticultura” and at nursery seedling of “Setor de Manejo Integrado de Pragas” of “Escola de Agronomia e Engenharia de Alimentos” from March to October 2012. Three experiments were conducted. First, to define the best dosage of polymer coating, the treatments were arranged in a 2 x 4 factorial, with two cultivars (Santa Clara and Kada Gigante) and four concentrations of polymer Disc AG Red L-203® (0, 50, 100 and 150 mL kg-1 seed). In the second, with the polymer concentration established, the potential adhesive film coating for seed treatment with paclobutrazol was determined through a 2 x 4 factorial arrangement, presence or absence of the coating polymer Disc AG Red L-203® (0 and 150 ml kg-1 seed) and four paclobutrazol concentration PBZ (0, 35, 70 and 105 mg L-1). In the third, the tomato seed conditioning with PBZ (50 mg L-1) and coating polymer Disc AG Red L-203® (150 mL kg-1 seed) were evaluated. The film coating promotes negative effects on germination of cultivar Santa Clara. The cultivate Kada Gigante obtained a superior performance to Santa Clara as the emergence of seedlings. The use of hydrophilic polymer (150 ml kg-1 seed) increased 4% seedling emergence compared to control. The PBZ resulted in reductions in 27% germination, 8% seedling emergence, 19% seedling height, 20% leaf area and in increase in the detection of chlorophyll of 24%, compared to control. Imbibition of seeds with PBZ, even with the presence of the polymer coating, harmed the speed of germination and seedling emergence. In conclusion, the effect of film coating on the germination of tomato seeds depends on the cultivar. The seed physiological potential can increased by the use of polymer coating, although it does not occur for the production of seedlings. PBZ is effective in seedling growth control, but affect the germination and seed vigor. The film coating as a vehicle for fixation of paclobutrazol is not indicated due to maintenance of reduced seedling emergence.